When it comes to history (On the trail of a find) (Eurasian Journal of History, Geography and Economics, 2023)
This article is about the discovery of the "ACIER UNIVERSEL" brand weapon, manufactured in Belgium in 1894, used by the participants of the national liberation movement in our country